2014
DOI: 10.1017/s1461145714000649
|View full text |Cite
|
Sign up to set email alerts
|

Raphe AMPA receptors and nicotinic acetylcholine receptors mediate ketamine-induced serotonin release in the rat prefrontal cortex

Abstract: Several lines of evidence indicate that ketamine has a rapid antidepressant-like effect in rodents and humans, but underlying mechanisms are unclear. In the present study, we investigated the effect of ketamine on serotonin (5-HT) release in the rat prefrontal cortex by in vivo microdialysis. A subcutaneous administration of ketamine (5 and 25 mg/kg) significantly increased the prefrontal 5-HT level in a dose-dependent manner, which was attenuated by local injection of α-amino-3-hydroxy-5-methyl-4-isoxazolepro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 24 publications
6
51
0
2
Order By: Relevance
“…The DRN contains the majority of the 5-HT neurons in the brain that are regulated by neural projections from various brain regions, including the PFC (Pollak Dorocic et al, 2014). Stimulation of the AMPA receptor expressed on the pyramidal neurons in the mPFC projecting to the DRN has been reported to activate the 5-HT neurons in the DRN (Martín-Ruiz et al, 2001), and AMPA receptor stimulation has been shown to be involved in the antidepressant effects as well as increase in 5-HT release in the mPFC by both mGlu2/3 receptor antagonists and ketamine Koike et al, 2011a, b;Maeng et al, 2008;Nishitani et al, 2014). Given that LY341495 and ketamine reportedly increase the release of glutamate in the PFC, presumably through inhibition of the autoreceptor in the glutamatergic nerve terminals for the case of LY341495 (Hascup et al, 2010) and disinhibition of pyramidal neurons in the PFC for the case of ketamine (Moghaddam et al, 1997), it is conceivable that both the mGlu2/3 receptor antagonist and ketamine activate postsynaptic AMPA receptor in the mPFC through enhancing the release of glutamate that may lead to subsequent activation of the 5-HTergic systems to exert antidepressant effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DRN contains the majority of the 5-HT neurons in the brain that are regulated by neural projections from various brain regions, including the PFC (Pollak Dorocic et al, 2014). Stimulation of the AMPA receptor expressed on the pyramidal neurons in the mPFC projecting to the DRN has been reported to activate the 5-HT neurons in the DRN (Martín-Ruiz et al, 2001), and AMPA receptor stimulation has been shown to be involved in the antidepressant effects as well as increase in 5-HT release in the mPFC by both mGlu2/3 receptor antagonists and ketamine Koike et al, 2011a, b;Maeng et al, 2008;Nishitani et al, 2014). Given that LY341495 and ketamine reportedly increase the release of glutamate in the PFC, presumably through inhibition of the autoreceptor in the glutamatergic nerve terminals for the case of LY341495 (Hascup et al, 2010) and disinhibition of pyramidal neurons in the PFC for the case of ketamine (Moghaddam et al, 1997), it is conceivable that both the mGlu2/3 receptor antagonist and ketamine activate postsynaptic AMPA receptor in the mPFC through enhancing the release of glutamate that may lead to subsequent activation of the 5-HTergic systems to exert antidepressant effects.…”
Section: Discussionmentioning
confidence: 99%
“…For the intracerebral microinjection experiments, LY341495 (0.003 and 0.03 pmol/0.1 μl/side) or ketamine (0.3 and 3 nmol/0.1 μl/side) was injected 30 min or 24 h before the test, and NBQX (0.01 and 0.03 nmol/0.1 μl/side) was injected 35 min before the test. The doses for the intracerebral microinjection of LY341495, ketamine, and NBQX were selected based on the observations in previous studies (Iijima et al, 2013;López-Gil et al, 2007;López-Gil et al, 2012;Nishitani et al, 2014).…”
Section: Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that enhancement of central serotonergic activity also underlies the antidepressant-like effects of ketamine [3]. Specifically, activation of the dorsal raphe nucleus (DRN) and subsequent serotonin (5-hydroxytryptamine; 5-HT) release in the PFC and the HIPP [5], is possibly implicated in the sustained antidepressant-like effects of ketamine in the FST [6].…”
Section: Research Highlightsmentioning
confidence: 99%
“…In primo luogo la ketamina ha dimostrato una bassa affinità per i recettori NMDA rispetto ad altri recettori, implicando che l'elevazione acuta del tono dell'umore debba essere dovuta ad altri meccanismi d'azione (Hillhouse 2014;Sanacora 2015). Questi potrebbero includere, nei mammiferi, l'effetto su target come i recettori per la rapamicina (mTOR; Li 2011b), il BDNF (Autry 2011), il sistema dopaminergico (Tan 2012), i recettori sigma (Robson 2012) e i recettori nicotinici dell'aceticolina (Nishitani 2014). In secondo luogo, se la ketamina avesse un efficace effetto antidepressivo, ci si aspetterebbe un'azione antidepressiva anche da altri antagonisti per i recettori NMDA, effetto non presente.…”
Section: Discussioni Sulla Teoria Del Glutammatounclassified